Pengaruh Kearifan Lokal Terhadap Penanaman Pendidikan Karakter Di Kelas X Madrasah Aliyah Nurul Karomah Paterongan Galis Bangkalan - hanafi, hanafi; Dian Eka Indriani; Anindita Trinura Novitasari (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2019)
This research is a quantitative descriptive study using data collection techniques, namely questionnaire / questionnaire, interview and observation. This research was conducted in class X Madrasah Aliyah Nurul Karomah Paterongan Galis Bangkalan, the results of this study to determine the effect of local wisdom in planti ng character education, forms of local wisdom and ways of planting character education in class X MA Nurul Karomah. Based on the analysis of the data obtained, conclusions show that there is an influence of local wisdom in the cultivation of character education class X MA Nurul Karomah, forms of wisdom in MA Nurul Karomah in the form of 1). Yellow Book Study. 2). Madura smooth engunt bunten. 2). Students stand up and say hello when the teacher wants to enter the class. Cultivation of character education is done through from class X by giving good examples to students.